Neuromuscular risk factors for knee and ankle ligament injuries in male youth soccer players - Read, P. J.; Oliver, J. L.; De Ste Croix, M. B. A.; Myer, G. D.; Lloyd, R. S. (Sports Medicine, 2016)
Injuries reported in male youth soccer players most commonly occur in the lower extremities, and include a high proportion of ligament sprains at the ankle and knee with a lower proportion of overuse injuries. There is currently a paucity of available literature that examines age- and sex-specific injury risk factors for such injuries within youth soccer players. Epidemiological data have reported movements that lead to non-contact ligament injury include running, twisting and turning, over-reaching and landing. Altered neuromuscular control during these actions has been suggested as a key mechanism in females and adult populations; however, data available in male soccer players is sparse. The focus of this article is to review the available literature and elucidate prevalent risk factors pertaining to male youth soccer players which may contribute to their relative risk of injury.